convert an expression into a string representation?

advertisements

Consider the following Haskell code:

module Expr where

    -- Variables are named by strings, assumed to be identifiers:

    type Variable = String

    -- Representation of expressions:

    data Expr = Const Integer
          | Var Variable
          | Plus Expr Expr
          | Minus Expr Expr
          | Mult Expr Expr
          deriving (Eq, Show)

    simplify :: Expr->Expr

    simplify (Mult (Const 0)(Var"x"))
     = Const 0
    simplify (Mult (Var "x") (Const 0))
     = Const 0
    simplify (Plus (Const 0) (Var "x"))
    = Var "x"
    simplify (Plus (Var "x") (Const 0))
     = Var "x"
    simplify (Mult (Const 1) (Var"x"))
    = Var "x"
    simplify (Mult(Var"x") (Const 1))
     = Var "x"
    simplify (Minus (Var"x") (Const 0))
     = Var "x"
    simplify (Plus (Const x) (Const y))
    = Const (x + y)
    simplify (Minus (Const x) (Const y))
    = Const (x - y)
    simplify (Mult (Const x) (Const y))
     = Const (x * y)
    simplify x = x

    toString :: Expr->String

How can I convert an expression to a string representation?

e.g.

toString (Var "x") = "x"
toString (Plus (Var "x") (Const 1)) = "x + 1"
toString (Mult (Plus (Var "x") (Const 1)) (Var "y"))
       = "(x + 1) * y"


Rather than call your function toString, it might be preferable to use the Show type class. Then your data type can be used anywhere that an instance of Show can be used. Show is the standard Haskell way of converting "things" into strings.

instance Show Expr where
    show (Var "x") = "x"
    -- etc.